1977
DOI: 10.1002/hlca.19770600423
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical reactions VII [1]. A ‘type A rearrangement’ in the photolysis of a steroidal α, β‐unsaturated lactone

Abstract: SummaryThe irradiation of 17~-hydroxy-2-oxa-androst-4-en-3-one (1) yields a cyclopropane derivative 2, which is the result of a rearrangement, formally analogous to the 'type A rearrangement' of the enones. Two other products, the dihydroxy compound 5 and the dimer 6, have also been isolated (Scheme I).The photochemical behaviour of the unsaturated lactones has been less widely studied than that of the corresponding ketones. Usually, these lactones dimerise by a well known and documented process [2]. More rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1977
1977
1981
1981

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In the monocyclic series, Matsuo et al have reported addition of the solvent in the irradiation of 5,6-dihydro-6-methyl-2Hpyran-2-one [3]. Recently, we have been able to show that the 2-oxa-d4 and 4-oxasteroidal lactones undergo, respectively, the type A [4] and di-z-methane [5] photorearrangements in a similar way to their carbocyclic counterparts. In this paper we describe the results obtained in the irradiation of the A'-lactone 1.…”
Section: Discussionmentioning
confidence: 96%
“…In the monocyclic series, Matsuo et al have reported addition of the solvent in the irradiation of 5,6-dihydro-6-methyl-2Hpyran-2-one [3]. Recently, we have been able to show that the 2-oxa-d4 and 4-oxasteroidal lactones undergo, respectively, the type A [4] and di-z-methane [5] photorearrangements in a similar way to their carbocyclic counterparts. In this paper we describe the results obtained in the irradiation of the A'-lactone 1.…”
Section: Discussionmentioning
confidence: 96%
“…irradiation of 17B-hydroxy-4a, 5 a -epoxy-2-azaandrostan-3-one (1) yields 17@-hydroxy-2-aza-l0 (5 + 4-abeo)-45 (H)-androsta-3,5-dione (3).Introduction. -We have reported that steroidal lactones behave photochemically in a similar way to their carbocyclic counterparts: a,B-unsaturated lactones, for example, undergo the 'type A' [2] and the di-z-methane [3] rearrangements, while a,@-epoxylactones suffer the 10 (5 4 4 ) rearrangement to an abeo structure [l]. Therefore, as a part of a systematic study on the photochemical behaviour of heterocyclic steroids, we investigated the UV.…”
mentioning
confidence: 99%